PENINGKATAN PENDAPATAN UMKM MASYARAKAT DESA DENGAN MENERAPKAN METODE BRANDING DAN PEMASARAN MELALUI MEDIA SOSIAL MASA PANDEMI COVID-19 - Adi Rosadi; Muh Hasan Marwiji; Dodi Supiyandi (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
The problem of empowerment of sukamaju village community nalindung subdistrict lacks awareness in developing and utilizing existing technology. The purpose of this research and development is to provide knowledge and insight into revenue-raising efforts by applying branding and marketing methods through social media. The methods used are the methods of discussion and practice and assistance to MSMEs. Activities are carried out in a duration of (approximately) 40 days (August 16-September 25). The result of this research is that these activities can help the community to expand the area of trading or selling livestock products and provide education about social media not only used to entertain but can also be profitable for lower middle-class entrepreneurs because in this day and age we must be smart to use social media well and usefull.